Growth performance, rumen development, and sensorial meat quality of goat kids fed extruded and pelleted starters - Rico-Costilla, Daniela S.; Ramos-Zayas, Yareellys; García-Hernández, Carlos; Méndez-Zamora, Gerardo; Fimbres-Durazo, Héctor; Moreno-Degollado, Gustavo; Kawas, Jorge R. (Frontiers in Animal Science, 2024)
The aim of this study was to determine the effects of supplementing extruded and pelleted starter feeds on growth performance, rumen development, carcass characteristics, and sensorial meat quality of goat kids fed an all-milk protein replacer. Forty-five new-born French Alpine kids (21 males, 4.93 ± 0.58 kg; and 24 females, 4.40 ± 0.60 kg) were randomly assigned to three treatment diets, milk replacer-only (RO), milk replacer supplemented with extruded starter feed (RE), or milk replacer supplemented with pelleted starter feed (RP) in a 3 x 2 factorial arrangement. After 35 days, the final weights, weight gain, body size measurements, organ weights, and hot and cold carcass weights were greater (p < 0.05) for goat kids in the RO group compared to those in the RE and RP groups. Milk replacer intake was reduced (p = 0.000) with starter supplementation, and intake of the extruded starter was higher (p = 0.001) than that of the pelleted starter. The rumen weight was greater (p = 0.019) in the RE group than in the RO group. Rumen pH was higher (p = 0.006) and acetic acid (p = 0.008) and total VFA (p = 0.012) concentrations were lower in the RO group than in the RE and RP groups. Mesenteric fat content was higher (p = 0.002) in the RO group than in the other groups. Meat odor of the RO group was preferred (p = 0.051) by the sensorial panel. Feeding an RO diet is beneficial for goat kids sold to restaurants. For replacement kids, an extruded starter feed may improve rumen development and facilitate adaptation to post-weaning dry feed consumption.